EFEKTIVITAS BEBERAPA SUMBER Β-KAROTEN YANG DICAMPURKAN PADA PAKAN TERHADAP PENINGKATAN KECERAHAN WARNA IKAN MAS KOKI Carassius auratus - Vega Lestari; Suci Puspita Sari; Ardiansyah Kurniawan (Journal of Aquatropica Asia, 2019)
This study aimed to test the effectiveness and determine the best effect of several sources of β-carotene mixed into the feed to the increase in brightness of colors in goldfish. This study uses a goldfish strain tosa size of ± 4 cm. This study used experimental method completely randomized design with five treatments and three replications. The negatif control treatment , the addition were given 3% carrot meal, 3% pumpkin meal, 3% spirulina meal and positif control treatment. Parameters was measured using Color picker to observed colouration enhance from body. The results showed that the addition of several sources of β-carotene to the diet provide the same effectiveness in improving the brightness of goldfish (Carassius auratus).